Description of Desmonostoc caucasicum sp. nov. (Cyanobacteria) using an integrative taxonomic approach - Maltseva, Svetlana Yu; Bachura, Yuliya; Erst, Tatyana V.; Kulikovskiy, Maxim S.; Maltsev, Yevhen (Phycologia)
A new cyanobacterial species of the genus Desmonostoc is described according to the International Code of Nomenclature for algae, fungi, and plants. The new species Desmonostoc caucasicum sp. nov. is recorded in the mountain meadow subalpine soil from the Greater Caucasus, Russia. The analysis is based on morphological characters, the 16S rRNA gene phylogenetic analysis, and ITS secondary structure. Desmonostoc caucasicum differs from the other species of the genus in colony morphology, size of vegetative cells and heterocytes, and habitat type. The 16S rRNA gene sequence of the new strain displayed 95.3%-97.9% similarities to other species of the genus Desmonostoc. The phylogeny inferred by maximum likelihood and Bayesian inference placed D. caucasicum in the Desmonostoc clade, within the Nostocaceae. The novel strain formed an independent lineage within the clade. The D1-D1MODIFIER LETTER PRIME, Box-B and V3 helices obtained from the 16S-23S ITS region didn't fit those of any described species of Desmonostoc. Amplification of a fragment of the mcy gene involved in microcystin biosynthesis from D. caucasicum confirmed that it has this genetic determinant. An integrative taxonomic approach, based on morphological, 16S rRNA and mcy genes molecular analyses, ITS secondary structure, along with ecological data, is used to delimit this new species.